Pengaruh viral marketing dan electronic word of mouth terhadap keputusan pembelian pada pengguna aplikasi shopee - Tapparan, Samuel Randy; Allo, Olga Firanda Taruk (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The research problem is how much influence Viral Marketing and Electronic Word Of Mouth have on Purchase Decisions for Shopee Application users. This study aims to determine the effect of Viral Marketing and Electronic Word Of Mouth on Purchase Decisions on Shopee Application Users among Students of the 2018 UKI Toraja Faculty of Economics Class Rantepao. The type of data used is Primary Data obtained from the results of questionnaires from respondents, namely Students of the Faculty of Economics UKI Toraja Class 2018 Rantepao Class as many as 50 respondents and Secondary Data obtained from the data and journals needed in this study. The research method used in this study is Multiple Linear Regression Analysis. The results show that both Viral Marketing and Electronic Word Of Mouth have a Stimulant and Partial effect on purchasing decisions.